Análisis bibliométrico sobre estudios epidemiológicos de quemaduras en Latinoamérica - Cubas Larco, Elizabeth (2023)
Objectives. To describe the scientific production on epidemiological studies of burns in Latin America in Scopus and Virtual Health Library databases from 1990 to July 2022. Materials and methods. Observational, descriptive and bibliometric design study. The Scopus and Virtual Health Library (VHL) databases were used, using Decs and Mesh. Data were extracted: annual publication, country, journal, year of publication, authors, collaboration, institution, journal impact factor, cite score, SJR, study design characteristics. The data selected from the search strategy were exported and descriptive statistics of frequency and percentage were obtained. VOSviewer software was used to generate maps and bibliometric networks for the variables of interest. Results. A total of 101 articles were evaluated in the VHL and 714 in Scopus, of which 15 and 362 original articles were found, respectively, that met the inclusion criteria. In 2020 where the highest number of publications was found in Scopus (n=31). The Burns Journal had the most publications (n= 54). Brazil is the largest Latin American country with studies on the subject (n=194) followed by Mexico (n=66). The country with the most current publications is Colombia covering the years between 2015 and 2021. The University of Sao Paulo was the institution with the highest number of publications (n=67). Articles published in the Journal Burns in 2017, were the most cited with 1,044 SJR and 4 Cite Score. Conclusions. Latin American articles in epidemiological studies on burns,especially after 2009, are promising.